Modelagem de propriedades termodinâmicas de soluções eletrolíticas aquosas pela equação de estado electrolattice - Zuber, André (2012)
Aqueous electrolyte solutions play an important role in many biological systems and have extensive application in a large number of industrial processes. An important example is the desalination of seawater into fresh water. This process is broadly found throughout Middle East and in different parts of the world where water scarcity is a problem that deserves attention. The principal methods used for desalination are evaporation and reverse osmosis. In both, vapor pressure, mean ionic activity coefficient, and osmotic coefficient are essential properties for their design, operation, and optimization. Equations of state (EOS) for electrolyte solutions are useful tools that enable, in principle, the evaluation of all such properties. Thereby, motivated by this argument, this dissertation includes the analysis of the electrolattice EOS applied to describe the behavior of electrolyte solutions. The equation was first derived by Santos (2010), based on the Helmholtz energy formalism. It contains three terms: the Mattedi-Tavares-Castier EOS term, applied to describe the short-range interactions between the species in the solution; the Born term, which considers the solvation of the ions; the mean spherical approximation (MSA) term, responsible for accounting the long-range interactions. In this research, 44 electrolyte aqueous solutions formed by a single salt of different specifications (such as 1:1, 1:2, 2:1, 2:2, and 3:1) are analyzed. The electrolattice EOS requires only two adjustable parameters to correlate vapor pressure and mean ionic activity coefficient for each solution. The parameters are determined by two different ways: the salt-specific and the ion-specific approaches. In both, the software named XSEOS and a program developed in FORTRAN are used for the regression step. Depending exclusively on the parameters obtained by theses regressions, the prediction of osmotic coefficient, at 298.15 K and 1 bar of aqueous solutions containing a single salt, is presented. Moreover, the model is tested to predict vapor pressure of aqueous electrolyte solutions containing two dissolved salts by using the ion specific parameters. In general, the results obtained with the electrolattice EOS are in good agreement with the experimental data